Democratic Ethics and Money Politics in Local Elections: An Islamic Legal Perspective - Wery Gusmansyah; Zulkarnain Syapal (Universitas Islam Negeri Raden Intan Lampung, 2025)
Democracy in the village head election in Kaur Regency has shifted from the principles of ideal democratic ethics (trustworthiness, honesty, justice, accountability) towards the practice of money politics, which has the potential to violate Islamic values. This study aims to analyze the ethics of democracy in the village head election in Kaur Regency and evaluate it from an Islamic legal perspective (Siyāsah Syari'iyyah). The research employs a juridical-empirical approach using a qualitative descriptive method. Data were collected through in-depth interviews with community leaders, election committee members, and village head candidates across several villages in Kaur Regency. The findings reveal that the practice of money politics occurs systematically in the village head election in Kaur Regency, where each candidate gives money to voters, including close family members, to win the election. According to Islamic law, the practice of money politics in village head elections is categorized as rishwah (haram), unless it is done with the intention of establishing justice and eliminating oppression, in accordance with the principle of sadd adz-zari'ah